Photosynthetic performance and anti-oxidative response of Cornus controversa seedlings under cadmium and lead stress - Huang, Xiaoxia; Jiang, Yonglei; Cheng, Xiaomao; Deng, Lilan; Liu, Xuncheng (Bangladesh Journal of Botany, 2018)
The photosynthetic efficiency of Cornus controversa leaves was decreased significantly under Cd treatment while it was not affected by Pb exposure. Cd decreased while Pb treatment increased the chlorophyll contents of Cornus controversa leaves. Furthermore, the peroxidase (GPX) activities were decreased after Cd treatment while elevated by Pb exposure in Cornus controvera seedlings. In addition, both Cd and Pb exposures increased the malondialdehyde (MDA) and proline contents and elevated the superoxide dismutase (SOD) activities of Cornus controvera seedlings. Collectively, these results indicated that Cornus controversa may be more tolerant to Pb than Cd toxicity. This finding will contribute to the evaluation of planting Cornus controversa in heavy metal polluted soil conditions.